Influence of the Ultrasonic Treatment on the Properties of Polybutylene Adipate Terephthalate, Modified by Antimicrobial Additive - Kirsh, Irina (Polymers (Basel), 2020)
Particular attention is paid to biodegradable materials from the environmental point of view and antimicrobial materials that ensure the microbiological safety of packaged products. The aim of the work was to study the properties of the composition, based on biodegradable polybutylene adipate terephthalate (PBAT) and the antimicrobial additive—birch bark extract (BBE). Test samples of materials were obtained on the laboratory extruder by extrusion with ultrasonic treatment of the melt. The concentration of the antimicrobial additive in the polymer matrix was 1 wt %. A complex research was carried out to study the structural, physico–mechanical characteristics, antimicrobial properties and biodegradability of the modified PBAT. Comparative assessment of the physico–mechanical characteristics of samples based on PBAT showed that the strength and elongation at break indices slightly decrease when the ultrasonic treatment of the melt is introduced. It was found out, that the antimicrobial additive in the composition of the polymer matrix at the concentration of 1 wt % has a static effect on the development of microorganisms on the surface of the studied modified films. Studies of the biodegradability of modified PBAT by composting for 4 months have shown that the decomposition period of modified materials increased, compared to pure PBAT. The developed modified polymer material can be recommended as an alternative replacement for materials based on polyethylene for food packaging.